Is Facebook's Advertising Data Accurate Enough for Use in Social Science Research? Insights from a Cross-National Online Survey. (6th November 2022) - Grow, André; Perrotta, Daniela; Del Fava, Emanuele; Cimentada, Jorge; Rampazzo, Francesco; Gil-Clavel, Sofia; Zagheni, Emilio; Flores, René D.; Ventura, Ilana; Weber, Ingmar
Abstract: Social scientists increasingly use Facebook's advertising platform for research, either in the form of conducting digital censuses of the general population, or for recruiting participants for survey research. Both approaches depend on the accuracy of the data that Facebook provides about its users, but little is known about how accurate these data are. We address this gap in a large-scale, cross-national online survey ( N = 137, 224), in which we compare self-reported and Facebook-classified demographic information (sex, age and region of residence). Our results suggest that Facebook's advertising platform can be fruitfully used for conducing social science research if additional steps are taken to assess the accuracy of the characteristics under consideration.